Penerapan Media Digital Audiovisual dalam Meningkatkan Keterampilan Berbicara Bahasa Jerman Siswa SMA Negeri 63 Maluku Tengah - Maruanaya, Rita Fransina; Apituley, Patresia Silvana; Akihary, Wilma (Gaba-Gaba : Jurnal Pengabdian Kepada Masyarakat dalam Bidang Pendidikan Bahasa dan Seni, 2025)
The Community Service Program at SMA Negeri 63 Central Maluku aims to improve students' German speaking skills through the application of audiovisual digital media. The implementation of this activity is motivated by the results of interviews with German language subject teachers, which show that teachers still have difficulties in implementing effective learning that can encourage students' interest in learning German, especially in improving their speaking skills. In addition, students are also less motivated to learn because the media used are still limited to textbooks and static images. Thus, the target of this training activity is SMA Negeri 63 Maluku Tengah class XI students, totaling 20 people. The methods used in learning by using audiovisual media are lecture, question and answer, group discussion, and dialogue. The results of this activity show that students are more motivated to learn German with the help of video media, where they are very enthusiastic to master the utterances and vocabulary related to the theme of introductions and do pronunciation exercises repeatedly, which leads to an increase in their German speaking skills. The conclusion that can be drawn from this activity is that learning German by using audiovisual digital media can have a positive impact on improving students' speaking skills. through this activity, the PKM team can provide recommendations for German language subject teachers to apply audiovisual digital media in German language learning activities.